Elucidating The Diagnostic And Therapeutic Potential Of An RNA Aptamer Against Human Pituitary Tumour Transforming Gene 1 - Sankar, Prabu Siva (2019)
Nucleic acid aptamers are a class of molecular recognition elements capable of target interaction at high specificity and affinity. This study was aimed to generate an RNA aptamer against the Human Pituitary Tumour Transforming Gene 1 (PTTG1) oncoprotein which can serve as a potential diagnostic and therapeutic tool. PTTG1 gene was first cloned into the pET14b vector to incorporate the small 6X Histidine tag. Protein expression and purification ensued with the E. coli Rosetta 2(DE3)pLysS strain under the urea denaturing method. The protein identity was confirmed by western blot using monoclonal anti-PTTG1 antibody. Intrinsic florescence spectra analysis and GST-pulldown interaction analysis with GST-p53 conferred signs of successful protein refolding. 11 SELEX cycles with dual partitioning strategy were performed with positive indication of enrichment. Sequencing of the cycle 8 pool revealed a putative aptamer (SECURA-3) which depicted binding to PTTG1. SECURA-3 had a dissociation constant estimated at 16.41 ± 6.4 nM. SECURA-3 was employed for development of aptamer-based diagnostic assays namely ALISA, aptamer-based dot blot, aptamer based western blot and aptahistostaining. SECURA-3 was extended with a poly A-tail at the 3’-end to functionally labelled with the biotin by hybridization with the biotin labelled oligo dT sequence. SECURA-3 aptamer demonstrated detection of up to 0.0256 nM PTTG1 in the direct ALISA assay and with the sandwich configuration, SECURA-3 demonstrated detection of PTTG1 up to 3.2 nM with the aptamer as the capturing agent and 16 nM with the aptamer as the detection agent.